Design of a safety and health management system at work for the company Mendomet S.A. based on the ISO 45001:2018 standard. - Merizalde Zamora, Yuri Humberto; Sánchez Chávez, Carlos Abel (Ingeniería Química y Desarrollo, 2024)
The present investigation is carried out in the company Mendomet S.A. with the purpose of proposing an Occupational Health and Safety (OSH) management system since it is facing a series of problems by not having and not knowing the ISO 45001: 2018 standard. Therefore, a theoretical review is generated highlighting the importance of organizational management, physical health and others. To achieve the object of study, a mixed approach is used with a type of descriptive, explanatory and documentary research that identifies the internal critical factors. It was obtained as a result that the absence of this regulation has incurred an increase in dangers, decrease in profitability and productivity. In addition, an IPER matrix is ​​applied where a high risk is established in the operational area of ​​the industry center, for which an action plan is established to improve and protect the physical integrity of its collaborators.
Keywords: Organizational management; SST; management system; IPER matrix; ISO standard